Two-year epidemiology of post-COVID-19 conditions in Bangladesh: a cohort study of post-COVID-19 from 12,925 SARS-CoV-2 cases between July and December 2021-2023 in Bangladesh - Altaf Hossain Sarker; Md. Feroz Kabir; K. M. Amran Hossain; Sharmila Jahan; Md. Zahid Hossain; Tofajjal Hossain; Sohel Ahmed; Raju Ahmed; Md. Waliul Islam; Iqbal Kabir Jahid (BMC, 2024)
Abstract Background Post-COVID-19 conditions (PCCs), also known as long COVID, is persistently debilitating disorders that need investigation on their incidence, morbidity, and case-fatality rate. Purpose The objectives of this cohort study were to determine the incidence, characteristics, case-fatality, morbidity, and recovery of post-COVID-19 symptoms throughout a two-year period of observation. Methods This was a population-based cohort study of post-COVID-19 cases among 12,925 SARS-CoV-2 positive individuals in eight administrative districts of Bangladesh between July and December 2021-2023. PCC was diagnosed according to WHO clinical diagnostic criteria, and the screening procedure was completed through a household screening process. Results The incidence of PCC was 3.6%, the case-fatality rate was 1.92%, and the recovery rate was 9.0%. The significant predictors of PCC morbidity were geographical distribution, vaccination, comorbidities, and a longer duration of symptoms or multiple symptoms (p < 0.05). Conclusion Nearly 465 out of 522 people suffering from PCC are persistent and have a significant disability. However, the rate of recovery was 9.0%. It is necessary to investigate approaches to improve the recovery of PCC in Bangladesh.